New perspectives on the internet : Comprehensive - Schneider, Gary P. 1952-; Evans, Jessica 1967- (Australia : Course Technology Cengage Learning, 2013)
Covers the three main web browsers including Internet Explorer 9, Mozilla Firefox 4, and Google Chrome. With a critical-thinking, problem-solving approach, this title helps students learn basic to advanced features of the Internet from Browser Basics to Electronic Commerce.
Tutorial 1: Browser Basics. Tutorial 2: Basic Communication on the Internet: Email. Tutorial 3: Using Web-Based Services for Communication. Tutorial 4: Searching the Web. Tutorial 5: Information Resources on the Web. Tutorial 6: User-Generated Content on the Internet. Tutorial 7: Security on the Internet and the Web. Tutorial 8: Wireless Networking and Security. Tutorial 9: Creating Effective Web Pages. Tutorial 10: Electronic Commerce. Appendix A: The Internet and the World Wide Web. Appendix B: Microsoft Outlook Express. Appendix C: Using Windows Mail. Additional Research Assignments (1-8). Glossdex. Task Reference.
computer bookfair2015
Includes index.
Keywords: Internet